A BIBLIOMETRIC ANALYSIS OF THE TERM “ISLAMIC SOCIAL REPORT”: RESEARCH CLASSIFICATION, RESEARCH TRENDS AND FUTURE DIRECTIONS - Mediawati, Elis; Tullah, Dewi Sarifah; Hasibuan, David HM; Triyono, Bambang (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This bibliometric analysis delves into the dynamic landscape of